Design and research of combined magnetron-ion-beam sputtering system - Dudin, S.; Tkachenko, O.; Shchybria, A.; Yakovin, S.; Zykov, A.; Yefymenko, N. (Вопросы атомной науки и техники, 2018)
The design and characteristics of a new combined magnetron-ion-beam sputtering system are presented. The system allows coating deposition both by means of magnetron discharge, and by sputtering of complex composite targets by high-energy ion beam. Computer simulation and optimization of magnetic field topology on the system,
which is common for the magnetron discharge and the Hall-type ion source, have been carried out. The ignition
curves, current-voltage characteristics of the system, in dependence on gas type and pressure, magnitude and topology of magnetic field have been researched both for autonomous operation of the planar magnetron discharge and
ion source and for their combination. Spatial distributions of ion current are also presented. Розроблено та досліджено характеристики нової комбінованої магнетронно-іонно-променевої розпорошувальної системи з питомими параметрами, які відповідають промисловому виробництву. Система дозволяє
наносити покриття як за допомогою магнетронного розряду, так і шляхом перерозпорошення складнокомпозиційних мішеней високоенергетичним іонним пучком. Досліджено криві запалювання, розрядні характеристики в залежності від типу та тиску робочого газу, величини та топології магнітного поля як при автономній, так і при сумісній роботі планарного магнетронного розряду та джерела іонів. Досліджені просторові розподіли потоків іонів. Разработаны и исследованы характеристики новой комбинированной магнетронно-ионно-лучевой распылительной системы с удельными параметрами, отвечающими требованиям промышленного производства. Система позволяет наносить покрытия как с помощью магнетронного разряда, так и путем перераспыления сложнокомпозиционных мишеней высокоэнергетическим ионным пучком. Исследованы кривые
зажигания, разрядные характеристики в зависимости от типа и давления рабочего газа, величины и топологии магнитного поля как при автономной, так и при совместной работе планарного магнетронного разряда и
источника ионов. Исследованы пространственные характеристики потоков ионов.